Những câu hỏi liên quan
Bảo Trân Nguyễn
Xem chi tiết
Adam Trần
Xem chi tiết
Đinh Tuấn Việt
17 tháng 7 2015 lúc 12:35

Vì \(\left(x-3\right)^{10}\ge0\) ; \(5\left(y-2\right)^{10}\ge0\)

Mà (x-3)^10+5(y-2)50=0

\(\Rightarrow\left(x-3\right)^{10}=0\) và \(5.\left(y-2\right)^{10}=0\)

\(\Rightarrow x-3=0\) và \(y-2=0\)

\(\Rightarrow x=3\) và \(y=2\)

Ngoc An Pham
Xem chi tiết
vũ thị ánh dương
Xem chi tiết
Huy Hoàng
8 tháng 5 2018 lúc 23:08

b/

Ta có \(\left(x-3\right)\left(x+\frac{1}{2}\right)>0\)

=> \(\orbr{\begin{cases}x-3>0\\x+\frac{1}{2}>0\end{cases}}\)=> \(\orbr{\begin{cases}x>3\\x>\frac{-1}{2}\end{cases}}\)

Teressa
Xem chi tiết
Bùi Lê Khánh Huyền
Xem chi tiết
Nguyễn Thị Phương Hoa
Xem chi tiết
Nguyễn Đức Mạnh
Xem chi tiết
Vũ Ngọc Huyền
Xem chi tiết